PENGARUH KUALITAS INFORMASI, KEMAMPUAN INDIVIDU DAN NORMA SUBJEKTIF TERHADAP MINAT MAHASISWA JURUSAN ADMINISTRASI NIAGA POLINEMA - Dwi Sudjanarti; Tri Istining Wardani; Umi Khabibah (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This research aims to analyze the influence of information quality, individual ability and subjective norms on student interest in using the internet as a reference source in preparing TA and thesis. This type of research is an explanatory research that shows the causal relationship between research variables by using hypothesis testing. The research population is the students of semester VI and VIII in Academic Year 2016/2017 with a sample of 76 respondents. The technique of collecting samples using random sampling and data collection using questionnaires. Based on the results of research, there is a significant influence between variable quality information, individual ability and subjective norms to behavioral intention in the use of the internet as a reference source simultaneously shown Fhitung value of 1.955> from Ftabel of 1.41. But partially there is no significant influence on the variable ability of the individual against the behavioral intention of internet usage as a reference source. Variable quality of information and subjective norms have significant influence on behavioral intention of internet usage as reference source.